A Study of Practices and Outcomes of HRM in Pakistan - DR. SAIMA BATOOL; YASIR KHAN; MUHAMMAD TAHIR; MUHAMMD IDRIS (Journal of Business & Tourism, 2021)
HRM is capable of employee’s development and enhanced organizational competitiveness, thus it can contribute positively for developing countries. However, there is poor understanding and limited research about HRM in developing countries context. Pakistan also embraced HRM almost a decade ago; however, the experience is producing mix results. The current study is carried out with the objective to assess the HRM Practices and the HRM outcomes in Pakistan. The study utilizing semi-structured interviews and data was collected from sixty HR Personnel working in various organizations. Key findings of the study are that despite implementation of different HRM practices, overall degree of HRM sophistication is low. Moreover, HRM is producing positive outcomes including diversity, better discipline, and superior performance. Some negative HRM outcomes including bureaucracy, corruption, and unnecessary control are also reported in this study. The results point towards limited sophistication of HRM function in Pakistan which needs to be increased in scope to produce more favorable outcomes.